The Aesthetic Of The Enternal Rhythme In Mihiar Al-Dulaimi's Poetry. (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
This reaearch deals with the ehternal rhythme and its beauty in the poetry of Mehiar Al-Dailami ,  poetry is a type of a literary arts, and the language of poetry will descend into a dull poeut without the use of music.Musical rhythem has vital role in changing the vocabularies. Images, rmotions into verse. It's very significant element among those elements which verse builton them.The circle of the poetic rhytem can't be strict to rhyme, rhythem but alse it expands to the enternal rhythme.Which gave it more magic in effects which are caused by sounds.This sounds are coming up between words from division, comforting repetition antagram and matching.Mihiar-Al Dulami is a brilliant poit he can use the figures of speech and make use of them in his Hijazis in a very skillful manner to give his poetry beauty and glamour and to increase the rhytheme of his cnternal tone to let her leave its great trace in both the listener and the receiver.So, we will stand in front of a great poet in combining poetry. Who has a good musical ear he made his listener dance on his pure musical tone in his verse.Mihiar is a great example for that.